Microstructure and Mechanical Properties of CK35 Steel by Using Nano Fluid (Water/TiO2) and Oil (SAE 10W40/TiO2) as Quenching Media (University of Thi-Qar Journal for Engineering Sciences, 2018)
Four different quenching media (water, oil(SAE 10W40), Water/TiO2 nanofluid and oil(SAE 10W40/TiO2) nanofluid were used to compare the influence of quenching media on the mechanical properties and microstructure of CK35 steel. The results have proved that the microstructure for nanofluid (water base) quenching and tempering sample is the combination of tempered martensite and retained austenite with best mechanical properties and for water quenching and tempering specimen is mostly tempered martensite. While for Nanofluid (oil base) quenching and tempering specimen the microstructure is the heterogeneous mixture of ferrite and perlite with formation of Fe3C during the quenching, while for oil quenching and tempering specimen is an equi-axed arrangement of ferrite grains with grainy spheroidized spots of cementite at the ferrite grains and along the grain boundaries.